Featured Front Cover. (17th September 2020) - Lu, Heli; Liu, Guifang; Zhang, Chuanrong; Okuda, Toshinori
Abstract : The cover image is based on the Special Issue Article Approaches to quantifying carbon emissions from degradation in pan‐tropic forests–Implications for effective REDD monitoring by Heli Lu et al., https://doi.org/10.1002/ldr.3333 .